Populist Trends on the world Stage: : Contextualizing the Populist World Order - Siddiquei, Md. Riyad (The Jahangirnagar Review, 2025)
The ‘populist world order’ challenges globalization, international institutions and the ‘neoliberal world order’. It is based on the concept of “elite against the people’. It emphasizes nationalism, sovereignty and anti-establishment ideology. The source of undemocratic political system of a country is the unprogressive social system of that country. And the social system is formed depending on the culture of that country. The behavior of citizens and the political system complement each other. In the larger sense, the government and the people are each responsible in their respective capacities, which is a consideration within the criterion of fairness. This qualitative study examines the populist trends on the world stage. The populist government of Georgia Meloni is promoting nationalist and right-wing activities, which are creating divisions in society and eroding democratic values while promoting the hegemony of the populist world order. Poland’s government is flouting EU law and fundamental human rights through populist policies, which has a negative impact on the country’s international relations. Mexico emphasizes national sovereignty, wealth redistribution and social justice, and at the same time opposes the liberal world order. Victor Orban is attacking Hungary’s freedom of speech, judiciary and media freedom with his populist regime, pushing the country towards an undemocratic environment. In 2021, the democratic government was ousted by a military coup in Myanmar. In 2022, a large-scale crackdown was carried out to suppress the movement against the mandatory hijab law in Iran. Ahead of Russia’s 2024 Presidential election, opposition political parties have been severely banned. A major political crisis has arisen in Venezuela in 2024 with Presidential elections. The 2020 Presidential election in Belarus has been accused of massive rigging by opposition political parties. In Hungary, Victor Orban controls the media and the judiciary. In Mali, the military overthrew the interim government in 2021. In 2022, President Roch Marc Christian Kabore was ousted in a military coup in Burkina Faso. Therefore, this study highlights the populist trends on the world stage based on secondary data.